Relatos de experiências de leitura de contos machadianos com mulheres aprisionadas - Lourenção, Valter Antonio [UNESP] (2013)
This dissertation presents the results of a survey conducted with incarcerated women and the reading of literary texts, with the proposal to provide them, by reading experience the possibility to expand their vision of the world and facilitate their return to the social environment. The tales read with the inmates were “Idéias de Canário” (A Canarys Ideas), “A agulha e a linha” (The Needle and the Threat”), “A igreja do diabo”. (The Devil’s Church”) all written by Machado de Assis. Different methodologies were adopted as for instance oral reports later recorded in a field journal, and these written reports delivered at the end of the reading activities, combined with a questionnaire and the reading of the staged tale “A agulha e a linha”, made it possible to characterize and get better acquainted to each participant as well as their thinking towards reading and its understanding thus the understanding of the world